EFISIENSI TEKNIS USAHATANI UBI KAYU DI LAHAN KERING KABUPATEN KARANGANYAR, PROVINSI JAWA TENGAH - Novitaningrum, Restie; Saputro, Fery Wisnu; Saputro, Wahyu Adhi (MEDIAGRO, 2022)
Cassava is the main food commodity after rice and corn which is the most important in development of food diversification to maintain national food security. Cassava production can be increased by increasing productivity through the right combination of production factors. This study aims to determine the technical efficiency and the factors that cause the technical inefficiency of farming in Karanganyar Regency dry land. The study was conducted in Wonorejo Village, Jatiyoso District, Karanganyar Regency in July 2022. 60 respondents was taken as samples consisting of 30 farmers who grew Jalak Towo cassava variety and 30 farmers who grew another cassava variety. Data were analyzed using stochastic frontier production function that was estimated with the Maximum Likelihood Estimation (MLE) method. The results showed that cassava farms in general was technically efficient. The average technical efficiency is 76.9% and 80% of farmers have achieved technical efficiency above 70%. There are still opportunities to improve technical efficiency. Farming experience and growing Jalak Towo cassava variety have positive effect on technical efficiency.